Ensuring irrigation water availability for off-season vegetable production in the face of competition from rural domestic water supplies in the commune of Lalo (Benin) - Djigbo Félicien Badou; Christophe Nouvewa; Christian Allé; Audrey Merveille Adango; Luc Ollivier Sintondji (Agricultural Water Management)
During the dry season in West Africa, balancing agricultural and domestic water needs becomes increasingly challenging due to the depletion of water resources, underscoring the urgency for sustainable water resource management strategies. This study, conducted at the Tovinou site in Lalo, Benin, evaluates borehole productivity, irrigation water availability, crop water requirements, and irrigation scheduling to optimise groundwater use for off-season agriculture. Integrating agronomic, climatic, hydrogeological, demographic, and water consumption data, the proposed irrigation plan allocates 24 % of the area to drip irrigation and 76 % to micro-sprinkler systems. Results show that a borehole operating at 85 % of its flow capacity (21.6 m3/h), effectively meets peak water demand in January, estimated at 5639.2 m3 (181.9 m3/d), with 15 % of the borehole flow allocated to domestic water supply. Rotational watering ensures crop water requirements are met, with irrigation durations ranging from 46 to 152 min for drip irrigation and from 37 to 440 min for micro-sprinkler irrigation, depending on growth stage and season. By balancing agricultural needs with domestic water demands, this study ensures a sustainable solution for both sectors. The proposed framework is scalable and has the potential to support off-season vegetable production while addressing increasing water demands in rural West Africa.